(untitled) (Indian Journal of Animal Production and Management, 2024)
Small ruminant production provides sustainable income to small and marginal farmers under rainfed agriculture in India. Supplementation of feed additives like probiotics and prebiotics can reduce the usage of antibiotics in sheep production. Keeping this in view an experiment was conducted to study the effect of probiotics (Saccharomyces cerevisiae and Lactobacillus sporengens) and Mannan oligosaccharahides (MOS) as prebiotics and combination of both probiotic and prebiotic as synbiotic supplementation on body weight gain in Nellore Brown lambs. Data on body weight was collected and analysed statistically for significance. The average daily gain in different treatment groups were recorded as 110.99±5.23g, 135.85±4.66g, 174.71±6.3g and 148.09±3.87g in Control, T1, T2 and T3 groups, respectively. Supplementation of probiotic, prebiotic and synbiotic have significant effect on daily body weight gain in Nellore brown lambs.